(untitled) (Journal of Applied Learning and Teaching, 2020)
As globalisation is progressively expanding in the fields of economy, politics, society and culture, so too is internationalisation in the sector of higher education (HE). This fact had instigated around the turn of the millennium an increasing interest in the concept of global citizenship also mirrored in the changes of educational strategies in HE. The number of HEIs that include, either in their mission statements the aspiration of developing global citizens, or explicitly embed global citizenship education into their curriculum has risen exponentially. However, because of the lack of a unanimous definition of global citizenship amongst scholars, there is much confusion about what this term entails or should entail. The most pertinent interpretation of global citizenship related to HE is that of the neoliberal approach which has received much critique mainly due to it perpetuating a Western/English-speaking hegemony or supremacy over the rest of the world and its lack of a justice-oriented approach. In agreement with scholars that urge for a critical approach to global citizenship as to counteract to the neoliberal approach, this conceptual paper will propose some practical examples of how critical global citizenship within HE could be fostered by focusing on the aspects of critical thinking and intercultural competence, drawing from the experience within the English for Academic Purposes classroom.